Early-Life Stress Alters Synaptic Plasticity and mTOR Signaling: Correlation With Anxiety-Like and Cognition-Related Behavior - Wang, Anfeng; Zou, Xiaojuan; Wu, Jiajia; Ma, Qingyu; Yuan, Naijun; Ding, Fengmin; Li, Xiaojuan; Chen, Jiaxu (Frontiers in Genetics, 2020)
Early life stress（ELS） predisposes individuals to the development of psychiatric disorders in later life,including anxiety, depression as well as cognitive impairments. However, the underlying molecular mechanisms are not completely understood.Developmental deficits in hippocampal synaptic plasticity are among the primary contributors of detrimental alterations in brain function induced by early-life stress. Impaired synaptic plasticity is usually accompanied by decreased synaptic proteins ,which is important for synaptic function,such as PSD95 and synaptophysin. The mTOR signaling pathway play a vital key in regulating protein translation, the activation of mTOR was functionally associated with synaptic protein synthesis. In the present study,we observe whether early life stress impact synaptic protein synthesis and the mTOR signaling,which is engaged in synaptic plasticity. Herein, we established maternal separation (MS) and chronic restraint stress(CRS) model and evaluate the anxiety-like behavior and cognition(eg.learning and memory) in adulthood period through behavioral examination and analyzed mRNA levels and proteins expression of PSD95 and synaptophysin in the hippocampus. To explore whether the mTOR signaling pathway is associated with ELS , we also examined the activity of mTOR and S6. The behavior tests indicted that maternally separated mice showed increased anxiety-like behaviour, cognitive impairments. PSD95,synaptophsin mRNA and protein expression levels was decreased in the hippocampus，as well as phosphorylated mTOR and phosphorylated S6 were decreased signically decreased in maternally separatation mice versus those non-exposed to maternal separatation. Our data demonstrate that early MS experience impaired synaptic plasticity and inhibited the mTOR sinaling pathway, specifically via S6. Therefore,we speculate that ELS dscresed synaptic plasticity via the inhibition of mTOR pathway in the hippocampus,which may underlie vulnerability to mental disorders in adulthood.